An experimental investigation of interrogative syntax/semantics - Kotek, Hadas; Hackl, Martin (Proceedings of the Amsterdam Colloquium, 2013)
Current theories of interrogative syntax/semantics adopt two strategies for the interpretation of in-situ wh-phrases: covert movement and in-situ interpretation. The covert movement strategy is traditionally assumed to be all-or-nothing: the in-situ wh-phrase covertly moves to C or else stays in-situ and is interpreted in its base-generated position at LF. In this paper we argue that neither approach to wh-in-situ can be maintained as is. We present evidence from real-time processing of English multiple wh-questions that in-situ wh-phrases require both covert movement and in-situ interpretation for their computation: an in-situ wh-phrase undergoes a short movement step, parallel to the behavior of traditional quanti ers such as every, immediately upon integration into the structure. Following that step, the wh-phrase can but need not move any further unless independent factors are at play. To account for this pattern we propose the partial movement approach to wh-in-situ: A wh-phrase must be interpreted at a position with propositional type at LF. Wh-phrases in object position are thus never interpreted in their base-generated position; instead some covert movement is always required.